Improving Fluidization Hydrodynamics of Group C Particles by Mixing with Group B Particles - Ebrahim H. Al-Ghurabi (Applied Sciences, 2018)
We have developed a new particle-mixing strategy for improving the fluidization hydrodynamics of Geldart group C powders by mixing with small proportions of group B particles. Two different group C particles with widely different physical properties, i.e., 1 μm calcium hydroxide powder and 27 μm porous activated carbon, were selected for investigation in the present work. A carefully sieved sample of inert sand was used as external group B particles for mixing. Fluidization experiments were carried out, and the quality of the fluidization was assessed using the fluidization index. For the monocomponent fluidization of fine calcium hydroxide powder, pressure drop was sometimes as much as 250% higher than the effective weight of the bed. The proposed strategy of particle mixing substantially improved its fluidization hydrodynamics. On the other hand, the development of channels and cracks during the monocomponent fluidization of the activated carbon led to gas bypassing, resulting in low pressure drop and poor contact of phases. Particle mixing was found to improve fluidization behavior, and the chi-squared test showed that the best results were obtained with 13 wt% particle mixing.